Thermoelectric performance and optimization of three-terminal quantum dot nano-devices. (15th January 2016) - Zhang, Yanchao; Wang, Yuan; Huang, Chuankun; Lin, Guoxing; Chen, Jincan
Abstract: The thermodynamic performance and optimization of a three-terminal quantum dot nano-device consisting of two capacitively coupled quantum dots connected to electron reservoirs in the Coulomb-blockade regime are investigated. Based on the master equation, the existing model with configuration A and a previously unreported model with configuration B of the device are studied and compared systematically. The maximum power output and efficiency of the two configurations under different given conditions are analyzed. The results obtained indicate that the working regions of the output voltage and Coulomb interaction of configuration B are significantly larger than those of configuration A. Moreover, the optimum ranges of the output voltage and Coulomb interaction of both configuration A and B are determined. A key measure of performance, i.e. the efficiency at the maximum power output, is further studied. It is found that the efficiency at the maximum power output is approximately equal to 0.035 for configuration A and 0.058 for configuration B. When the temperature difference between the two electron reservoirs is large enough, the maximum power output and efficiency at the maximum power output of configuration B are significantly larger than those of configuration A. Highlights: Two configurations of three-terminal quantum dot engines are established. Effects of the output voltage and Coulomb interaction are discussed. Maximum power outputs and efficiencies of two configurations are calculated. Performances of two configurations are optimally analyzed and compared. Optimum ranges of the output voltage and Coulomb interaction are determined.